Monitoring Non-Communicable Diseases (NCDs) Through Blood Glucose and Uric Acid Tests in the Elderly - Rr. Sri Isjworowati; Nida Fatma M; Rainy Delima; Raz Gaura JW (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2026)
Non-Communicable Diseases (NCDs) such as Diabetes Mellitus and Gout pose a serious threat to the health of the elderly due to their often asymptomatic nature. Cost barriers hinder the elderly community from accessing laboratory services. This community service activity aims to improve health standards and early detection of NCDs through monitoring blood glucose and uric acid levels in the Generasi Kaleb community of the JKI Injil Kerajaan Church, Semarang. The Participatory Health Screening and Education method used includes health education, screening using the Point of Care Testing (POCT) tool, and personal consultation on the results. The service subjects were 50 elderly respondents. The examination results showed a prevalence of abnormal random blood glucose (GDS) of 8%, 32%, had high uric acid levels with a maximum value of 10.3 mg/dL. This activity successfully transformed the elderly's awareness from subjective perception to awareness based on objective data, and encouraged community independence in managing a healthy lifestyle to prevent further NCD complications. .